Grammar Errors Made by Micro Teaching Students: A Case at English Department of UNP - Yuli Tiarina (Universitas Negeri Padang, 2014)
The writer saw the problem when the writer was doing a research on applying reflective teaching to improve students’ pedagogic competency in teaching practice in Micro Teaching subject. For the first and second meetings, the students were asked to comment their friend who had just finished teching practice for interactional text. It was found that most students commented on their teaching technique, media and material. None commented on their grammar error, whereas it was found many grammar errors that will lead to wrong exposure later. They are going to be teachers. They should have linguistic competence as well. Then, an error analysis is needed to see what error made most by students. It is hoped that by analyising the errror that students will know them, and it can the feedback for them. This descriptive qualitative study is to analyze what types errors most made by the subject of this study. In this errors analysis, a Target Modification Taxonomy by James (1998) is to analyze and describe the errors. The students spoken language were recorded and transcribed before analysis took place to gain the data of this error analysis study. Theory of qualitative data proposed by Ary (2010) is implemented in analyzing the data of this study. It was found that the errors made most by Micro Teaching students are misselection.